Application of PCR-based methods for diagnosis of intestinal parasitic infections in the clinical laboratory. Issue 14 (29th April 2014) - VERWEIJ, JACO J.
SUMMARY: For many years PCR- and other DNA-based methods of pathogen detection have been available in most clinical microbiology laboratories; however, until recently these tools were not routinely exploited for the diagnosis of parasitic infections. Laboratories were initially reluctant to implement PCR as incorporation of such assays within the algorithm of tools available for the most accurate diagnosis of a large variety of parasites was unclear. With regard to diagnosis of intestinal parasitic infections, the diversity of parasites that one can expect in most settings is far less than the parasitological textbooks would have you believe, hence developing a simplified diagnostic triage is feasible. Therefore the classical algorithm based on population, patient groups, use of immuno-suppressive drugs, travel history etc. is also applicable to decide when to perform and which additional techniques are to be used, if a multiplex PCR panel is used as a first-line screening diagnostic.